Correlation of mandibular canal wall resorption with angular cortical thickness among edentulous patients using panoramic radiographs (A comparative study between male and female) (Mustansiria Dental Journal, 2018)
BackgroundResorption of alveolar bone is the best recognized feature of mandibular aging inthe edentate subject. The aim of this is study to evaluate the mandibular canal wallresorption using panoramic radiographs among edentulous male and female.Material and methodThe sample of this study was collected from patients who attended TeachingHospital of the College of Dentistry at Al- Mustansiria University and panoramicradiographs were taken in Al-Karama specialized center for dentistry. Forty threepatients were selected in this study with age range between 59-85 years (25 malesand 18 females) . Panoramic radiographs for all patients and sides were examinedand evaluated .ResultsChi-square between males and females of angular cortical thickness (ACT) ≥1mm and ACT ˂ 1mm was (37.06) which statistically significant with p-value(0.008) and between resorption (grades) and age of males was(34.72) which itstatistically significant p-value(0.049) also between resorption (grades) and age offemales was(15.6) which was statistically significant p-value (0.003) . Spermancorrelation showed statistically significant moderate correlation between gender andage (r=0.581,p-value=0.01) and there was a moderately statistical significantcorrelation between the grades of mandibular canal resorption and the angularcortical thickness measurements in both gender (r=0.532,p-value=0.033).ConclusionThe resorption of the wall is found more often in edentulous females than in themales due to hormonal imbalance.